Zachowania zdrowotne studentów Dietetyki = Health behaviors of students of Dietetics - Weber-Rajek, Magdalena; Radzimińska, Agnieszka; Kalisz, Zdzisława; Hoffmann, Magdalena; Juraszek, Karolina; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Weber-Rajek Magdalena, Radzimińska Agnieszka, Kalisz Zdzisława, Hoffmann Magdalena, Juraszek Karolina, Goch Aleksander, Zukow Walery. Zachowania zdrowotne studentów Dietetyki = Health behaviors of students of Dietetics. Journal of Education, Health and Sport. 2016;6(6):469-477. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56236 http://ojs.ukw.edu.pl/index.php/johs/article/view/3619 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Zachowania zdrowotne studentów Dietetyki Health behaviors of students of Dietetics Magdalena Weber-Rajek1, Agnieszka Radzimińska1, Zdzisława Kalisz2, Magdalena Hoffmann3, Karolina Juraszek4, Aleksander Goch5, Walery Zukow6 1. Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Bydgoska Szkoła Wyższa w Bydgoszczy 3. Uniwersyteckie Centrum Kliniczne w Gdańsku, Klinika Nadciśnienia Tętniczego i Diabetologii 4. Centrum Onkologii im. prof. F. Łukaszczyka w Bydgoszczy, Zakład Rehabilitacji 5. Katedra Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 6. Uniwersytet Mikołaja Kopernika w Toruniu Słowa kluczowe: zachowania zdrowotne, studenci. Key words: health behaviors, students. Streszczenie Bardzo ważną rolę w procesie ochrony zdrowia jest styl życia człowieka – jego nawyki oraz wzorce postępowania. Celem badań była ocena zachowań zdrowotnych studentów kierunku Dietetyka. Grupę badawczą (Grupa I) stanowiło 80 studentów kierunku Dietetyka. Grupę porównawczą (Grupa II) stanowiło 70 studentów kierunków „niemedycznych” (kierunki inżynierskie). W grupie studentów Dietetyki uzyskano wysoki poziom zachowań zdrowotnych. Najwyższy poziom zachowań zdrowotnych uzyskano w kategorii „prawidłowe nawyki żywieniowe”. Studenci kierunku Dietetyka uzyskali wyższe wyniki zachowań zdrowotnych od studentów kierunków inżynierskich. Wprowadzanie programów promocji zdrowia i edukacji zdrowotnej powinno objąć wszystkie kierunki studiów, tym bardziej, że wczesna dorosłość jest najlepszym okresem dla osiągnięcia długotrwałych korzyści z wyboru zdrowego trybu życia. Summary Very important role in the protection of health is a lifestyle - habits and patterns of conduct. The aim of the study was to assess health behaviors of Dietetics students. The research group (Group I) conducted of 80 students of Dietetics. The control group (Group II) conducted of 70 students of non-medical (in engineering). In the group of Dietetic student achieved a high level of health behaviors. The highest level of health behaviors was achieved in the category of "nutrition habits." Students of Dietetics scored higher health behavior of engineering students. Entering programs of health promotion and health education should be extended to all fields of study, especially that early adulthood is the best time to achieve long-term benefits of a healthy lifestyle choice.